Investigating the Effects of Financial Inclusion: A Systematic Review (Quest Journal of Management and Social Sciences, 2024)
Background: Financial inclusion is a key enabler of Sustainable Development Goals (SDGs) for 2030, and it is said that inclusion through savings mobilisation for investment and consumption can boost growth and contribute to the SDGs. However, further evidence is required to claim that financial inclusion can help overall economic growth and achieve larger development goals as envisioned by SGDs.Objective: This research aims to comprehensively review existing literature on the effects of financial inclusion, emphasising its role in supporting economic growth and contributing to broader development goals.Methods: A systematic literature review was conducted using the Scopus database, covering papers published up to 2023. A total of 264 papers were extracted, and a refined selection of 103 papers was made based on pre-defined inclusion and exclusion criteria. The chosen papers were subjected to further analysis.Results: The results reveal that the number of studies on the effects of financial inclusion has v financial inclusion significantly affects each variable. The findings also underscore the multifaceted impact of financial inclusion, emphasising its role in fostering SMEs, influencing macroeconomic indicators, bolstering the stability of banks, and positively affecting the population's socioeconomic status.Conclusions: This study concludes that financial inclusion is a key driver for achieving sustainable development goals, particularly for emerging economies. This research synthesis contributes to a deeper understanding of the diverse implications of financial inclusion.Paper Type: Review PaperJEL Classification: G20, F63, I30